Exploring women’s perception on birth process through body mapping - Shahaduzzaman; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2020)
To explore women's perception on birth process 'body mapping' exercise was conducted with three different categories of rural women; trained traditional birth attendants (TBA), untrained TBAs and women who had never attended any delivery. There were 20 women in each category. Each was given a paper with the outline of a women's body and asked to draw what she imagined about the inside of a pregnant woman to look like. After completion of the drawing, each was asked to label and explain her drawings. The 'body mapping' helped to reveal the diversity of women's perception of the birth process, which would have been difficult to obtain. The drawings highlighted the difference and similarities between biomedical and indigenous concepts. By comparing the body maps done by the three categories of women, it appeared that the perception of the trained TBAs was more consistent with the biomedical model. However, some common patterns of perception and differences in scientific and indigenous vocabulary was found in all categories of women. It appears from the study that body maps have a range of potential uses as a research technique to explore lay perceptions on different health issues and as a tool for training and evaluation.